Translated Poetry in Late Soviet Latvia: sporadic modernism and the construction of world literature - Ivars Šteinbergs (Respectus Philologicus, 2024)
The article builds upon previous work that has been written about the connection between translation and colonial endeavours (Tymoczko, 1999; Robinson, 2014), as well as the research done in the field of Baltic post-colonialism (Annus, 2018), and focuses on cases of poetic production in Soviet Latvia during the time after de-Stalinization. By surveying data on the publication of books of translated poetry in Latvia after 1956 – when knowledge of Stalin’s terror disseminated, the study reveals how translation was used to strengthen Soviet power in occupied territories. The “world” that was being represented through translation was largely Eurocentric and Russocentric. Simultaneously, from the 1960s onward, several Latvian translators wrote translations and poems that survive both as documents of cultural others, and as testimonies of local noncompliance. These works are imbued with modernist poetics that was unfamiliar to or even condemned by the propagators of socialist realism, the official and ideologically saturated aesthetic promoted by the Soviet regime. The article suggests reading such texts as a kind of sporadic modernism within Soviet Latvia.